2006
DOI: 10.1177/0011392106056747
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Relationships and Elderly Care in China

Abstract: Based on a review of recent research literature, major value-practice conflicts toward elderly care in China are explored, some commonalities and differentiations of real practices with traditional values are presented, the emerging new values in intergenerational relationships are discussed, and the theoretical underpinnings of interdependency are examined. Some sociologists had predicted a continuing decrease in family interdependence and caregiving. In the current globalization of economic development and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 17 publications
2
69
0
Order By: Relevance
“…They found their current lives, with challenges, were more interesting and less lonely and isolated. In fact, in some cases the two sets of grandparents competed for the opportunity to nurture and care for their grandchildren (Sheng and Settles, 2006). They ended up rotating their care work for their grandchildren.…”
Section: Grandparenting In the Chinese Cultural Contextmentioning
confidence: 99%
“…They found their current lives, with challenges, were more interesting and less lonely and isolated. In fact, in some cases the two sets of grandparents competed for the opportunity to nurture and care for their grandchildren (Sheng and Settles, 2006). They ended up rotating their care work for their grandchildren.…”
Section: Grandparenting In the Chinese Cultural Contextmentioning
confidence: 99%
“…While in many traditional and developing countries such as China and Korea sons are considered to be the most important supporters of elder parents, recent studies in China indicate that daughters are the main source of instrumental support for their parents and they are more likely to provide financial support for them when they live far away from them (Sheng and Settles 2006). Women are more inclined to maintain stronger social relationships with family members (Aldous 1987).…”
Section: Theories Of Intergenerational Relationship and Supportmentioning
confidence: 99%
“…The traditional Chinese family is a co-residence among three generations of family members. However, co-residence among intergenerational family is becoming increasingly rare as young adults migrate to other regions seeking better employment opportunities [8]. Studies have shown that older parents continue to desire traditional family relations, such as the assistance of their children with housework, being able to care for their grandchildren [11], and keeping mutually close contact with their working children [10].…”
Section: Introductionmentioning
confidence: 99%